Tip force and pressure distribution analysis of a deployable boom during blossoming. (1st June 2020) - Wang, Sicong; Schenk, Mark; Guo, Hongwei; Viquerat, Andrew
Abstract: Deployable coilable booms have many advantages for use in space, but these kinds of structures sometimes experience a deployment failure mode called 'blossoming'. Blossoming of a coiled boom occurs when the boom stops deploying, and instead unwinds and expands within the deployer. This can occur even in the presence of sprung rollers used to constrain the coil. In the blossoming process, friction between the layers of the coil plays an important role that has only been briefly considered in previous work. In order to be able to model and predict the onset of this phenomenon more precisely, the pressure distribution between adjacent layers of the coil must be known. This paper establishes a numerical model to investigate the pressure distribution within a coiled open-section tape spring boom, then combines this result with theoretical analysis to produce an estimate of the maximum tip force that a deploying boom can withstand before the onset of blossoming. The effect of the roller springs' stiffness and the boom friction coefficient are also taken into account in the simulation. The results of the theoretical analysis and numerical simulation are compared with previous experimental results to provide some practical verification.